Public transport planning tool for users on the autism spectrum: from concept to prototype. (17th February 2021) - Rezae, Mortaza; McMeekin, David; Tan, Tele; Krishna, Aneesh; Lee, Hoe; Falkmer, Torbjorn
Abstract: Purpose: This research explored the challenges of public transport use for individuals on the autism spectrum. It, subsequently, proposed a mobile application solution, coproduced by individuals on the autism spectrum, to facilitate public transport use. Methods: We, first, conducted a review of the literature to highlight the challenges people on the autism spectrum face when utilizing public transport. We, then, designed a list of mobile application functionalities that address the identified problems. To validate these functionalities, 27 young autistic adults and 19 families of autistic individuals were employed. Finally, based on the findings, we designed a mobile application that helps facilitate public transport use for those on the autism spectrum. Results: We found that the most prevalent concerns, in public transport use, amongst autistic individuals and their families are safety and spatial awareness. Specific problems include finding one's way to the bus stop, boarding the correct service and disembarking at the correct stop. Interestingly, anxiety about unexpected events was also a barrier. Sensory sensitivity, similarly, was found to be an obstacle. Conclusions: This study defined the challenges of public transport use for autistic individuals and proposed a technological solution. The findings can also inform innovators, public transport providers and policymakers to improve public transport accessibility. Implications for rehabilitation: People on the autism spectrum heavily rely on other individuals, namely family and friends, for their transportation needs. This dependence results in immobility for the autistic individuals and significant time and economical sacrifice for the person responsible for the transportation. Public transport, a cheap and widely available form of transportation, has not yet been clearly studied with individuals on the autism spectrum. We clearly define the challenges of using public transport and put forward a trip planner mobile application, coproduced by autistic individuals, that facilitate it. In the long term, this enhanced travel independence can lead to greater education and employment opportunities and an overall improved quality of life.